Bit-interleaved space-time coded modulation with iterative decoding. - Zhihong Hong (IEEE Transactions on wireless communications)
Bit-interleaved space-time coded modulation (BI-STC), which combines serial concatenation of bit-interleaved coded modulation (BICM) with space-time block codes, can effectively exploit the available diversity in space and time under various fading conditions. In this letter, we propose to use iterative decoding to further improve the performance of BI-STC by exploiting the concatenating structure of the codes. The decoding metric is therefore modified to fit for the iterative process, and the derived error bounds suggest that set-partition labeling instead of gray labeling should be used when considering iterative decoding.